Microbially influenced corrosion of SS304 steel by mixed microbial communities in a novel electrochemical flow cell system - Chai, Mei Yi, Rosalie (2016)
Microbially influenced corrosion (MIC) is the process of metal deterioration resulting from exposure to microorganisms and their metabolites. The ability of microorganisms to alter redox reactions, leading to accelerated corrosion rate, has strong economic and environmental impacts. MIC is particularly relevant in seawater, as its high salinity and conductivity confer to seawater the characteristic of an electrolyte, thus facilitating corrosion reactions. Most MIC studies have used electrochemical batch cells inoculated with a single species. Thus, the effects on MIC as a consequence of the complex interactions in a mixed microbial biofilm remains poorly understood. In this study, a novel electrochemical flow cell (EFC) was developed to investigate the MIC of SS304 steel by a mixed marine microbial community. MIC was characterized with a combination of electrochemical and microscopy techniques. Short-term experiments (≤7 d) were conducted to analyze the effects of nutrient composition on the initial MIC rate of the metal coupons in the presence of a mixed microbial seawater community. Results from linear polarization (LP), electrochemical impedance spectrometry (EIS) and open circuit voltage (OCV) analysis show that readily available organic nutrients (glucose) enhance MIC rates. This may be attributed to faster microbial growth, resulting in pH and oxygen concentration gradients across the biofilm. These results also validate the EFC for the study of MIC. Complementary metagenomics and meta-transcriptomics analysis are ongoing to reveal the role of the microbial community in MIC process.